Overview of Substance Use and Mental Health Among the "Baby Boomers" Generation. (2nd January 2017) - Cleary, Michelle; Sayers, Jan; Bramble, Marguerite; Jackson, Debra; Lopez, Violeta
Abstract : As the population ages, risk factors commonly shared by chronic degenerative disease can be exacerbated by behaviours and lifestyle choices. There is increasing evidence that those affected by chronic disease (and associated symptoms such as pain), depression and adverse behavioural and lifestyle patterns are at risk of substance misuse. This paper overviews substance use in Baby Boomers, which are defined as people aged between 52–70 years old, and the implications this may have on their mental health and well-being. We provide an overview of the characteristics of the Baby Boomer generation, their health status and what is currently known about their substance use and misuse. A strengthening of older adult mental health outpatient services is recommended to prevent and address substance use among older adults. Further research examining factors that influence substance use among this group could better inform health promotion programs targeting Baby Boomers.